Decoupling of latitudinal gradients in species and genus geographic range size: a signature of clade range expansion. Issue 3 (2nd November 2016) - Tomašových, Adam; Jablonski, David
Abstract: Aim: Clade range size is a function of species range sizes but also depends on the geographic deployment of species: clade range expansion should therefore depend partly on the tendency of a clade to produce new species. Previous work has shown empirically that species‐rich clades are more likely to expand outside their present distributions, i.e. to overcome niche conservatism, than species‐poor ones. This pattern can follow from a neutral probabilistic model of clade‐level range expansion arising from differences in net species diversification between clades. We show that predictions of this model discriminate between weaker and stronger climatic niche conservatism, and compare these predictions with range‐size patterns of marine bivalves at the species and clade (genus) level. Location: Western Pacific, eastern Pacific and western Atlantic. Methods: We decompose the latitudinal and thermal distribution of genera into within‐species and among‐species components. We use a neutral model in which species range expansion does not vary with latitude and descendants originate within the ranges of their ancestors (model with spatial dependency) or where descendants originate independently of ancestral ranges (model without spatial dependency). Result: In accord with model predictions: (1) genus latitudinal range size is weakly related to the latitudinal range sizes of congeneric species, but strongly depends on per‐genus species richness; (2) among‐species latitudinal distances correlate positively with per‐genus species richness; and (3) genus latitudinal and thermal range sizes increase towards higher latitudes because genera that are species rich anywhere within their range increase in proportion towards higher latitudes. Main conclusions: Application of the neutral probabilistic model to marine bivalves shows that tropical niche conservatism is only moderately strong, and that species diversification plays a significant role in range expansion of bivalve genera to new latitudes and climates, even when thermal range sizes and limits of congeneric species show significant correlations, and are thus conserved to some degree.